2019
DOI: 10.1029/2018gl081550
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of EMIC Wave‐Driven Scattering Loss of Ring Current Protons to Wave Normal Angle Distribution

Abstract: Electromagnetic ion cyclotron waves have long been recognized to play a crucial role in the dynamic loss of ring current protons. While the field‐aligned propagation approximation of electromagnetic ion cyclotron waves was widely used to quantify the scattering loss of ring current protons, in this study, we find that the wave normal distribution strongly affects the pitch angle scattering efficiency of protons. Increase of peak normal angle or angular width can considerably reduce the scattering rates of ≤10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 65 publications
1
49
0
Order By: Relevance
“…These two models are further assumed latitudinally constant. The third model follows previous studies (e.g., Cao et al, ; Ni et al, ) to include the latitudinal variation of hiss wave normal angle distribution confined within 40° of the magnetic equator, which is based on the formation of hiss waves due to the propagation penetration of whistler mode chorus into the plasmasphere (Bortnik et al, , , ; Chen et al, ). As shown in Figures a–i, the diffusion rates caused by plasmaspheric hiss with the small wave normal angle distribution (left column) and latitudinally varying wave normal angle distribution (middle column) have similar profiles in the ( E k , α 0 ) space, driving efficient pitch angle scattering of tens of kiloelectronvolts to hundreds of kiloelectronvolts electrons near the equatorial loss cone at rates of >~10 −5 s −1 .…”
Section: Sensitivity Analysismentioning
confidence: 98%
“…These two models are further assumed latitudinally constant. The third model follows previous studies (e.g., Cao et al, ; Ni et al, ) to include the latitudinal variation of hiss wave normal angle distribution confined within 40° of the magnetic equator, which is based on the formation of hiss waves due to the propagation penetration of whistler mode chorus into the plasmasphere (Bortnik et al, , , ; Chen et al, ). As shown in Figures a–i, the diffusion rates caused by plasmaspheric hiss with the small wave normal angle distribution (left column) and latitudinally varying wave normal angle distribution (middle column) have similar profiles in the ( E k , α 0 ) space, driving efficient pitch angle scattering of tens of kiloelectronvolts to hundreds of kiloelectronvolts electrons near the equatorial loss cone at rates of >~10 −5 s −1 .…”
Section: Sensitivity Analysismentioning
confidence: 98%
“…The polarization reversal at the crossover frequency will significantly modify the dispersive properties of EMIC waves at high latitudes and may subsequently affect the EMIC wave‐driven scattering of magnetospheric particles. However, in the calculations of quasi‐linear bounce‐averaged particle diffusion coefficients, previous studies commonly assumed that EMIC waves are purely left‐hand polarized for both strictly parallel propagating (e.g., Ni et al, 2018; Summers & Thorne, 2003; Ukhorskiy et al, 2010; Usanova et al, 2014; Xiao et al, 2012) and obliquely propagating events (e.g., Albert, 2003; Cao et al, 2016, 2019; Capannolo et al, 2019; Glauert & Horne, 2005; He et al, 2016; Ni et al, 2015; Uzbekov et al, 2016). Some recent studies also assumed that EMIC waves are confined to below the geomagnetic latitudes where the polarization reversal can occur (e.g., Ma et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple satellite observations have indicated the heating of helium (He + ) and proton (H + ) ions at thermal energies of several hundred eV by EMIC waves and magnetosonic waves in the magnetosphere (Anderson & Fuselier, ; Fuselier & Anderson, ; Mauk et al, ; Mouikis et al, ; Roux et al, ; Young et al, ; Yuan et al, ; Zhang et al, ). Resonant interaction analyses, using both theory and numerical modeling, have suggested the possible ion scattering and acceleration at ring current energies or thermal energies associated with EMIC waves and magnetosonic waves, because the Doppler‐shifted wave frequency could be close to the ion gyrofrequency or its harmonics (Bortnik et al, ; Cao et al, , ; Fu et al, ; Gendrin & Roux, ; Isenberg, ). In addition, the ray‐tracing simulations have indicated that EMIC waves could be absorbed by the thermal ions as their wave normal angles become oblique on their propagation path (Horne & Thorne, ; Thorne & Horne, ), and that radially propagating magnetosonic waves could heat the thermal protons (Horne et al, ).…”
Section: Introductionmentioning
confidence: 99%